In vitro evaluation of suspoemulsions for in situ-forming polymeric microspheres and controlled release of progesterone. (18th August 2015) - Turino, Ludmila N.; Mariano, Rodolfo N.; Mengatto, Luciano N.; Luna, Julio A.
Abstract: One possibility to obtain a higher dose of drug in a lower formulation volume can be by using of saturated quantity of drug in one of the phases of an emulsion. These formulations are called suspoemulsions (S/O/W). When a hydrophobic polymer is added to the organic phase of suspoemulsions, these formulations can be used to entrap the drug inside microspheres after in situ precipitation of the polymer–drug–excipients mix. In this work, performance and stability of progesterone suspensions in triacetin as organic phase of suspoemulsions were evaluated. These formulations were compared with O/W emulsions. Mathematical models were used to study in vitro release profiles. The results confirmed that S/O/W systems could be an attractive alternative to O/W formulations for the entrapment of progesterone inside poly(d, l -lactide- co -glycolide) microspheres. Diffusive-based models fit the in vitro release of progesterone from in situ -formed microspheres. For longer release periods, a time-dependent diffusion coefficient was successfully estimated.